Bullous pemphigoid and dipeptidyl peptidase IV inhibitors: a case–noncase study in the French Pharmacovigilance Database. (19th July 2016) - Béné, J.; Moulis, G.; Bennani, I.; Auffret, M.; Coupe, P.; Babai, S.; Hillaire‐Buys, D.; Micallef, J.; Gautier, S.; ,
Summary: Background: Inhibitors of dipeptidyl peptidase (DPP)‐IV have been suspected in the onset of bullous pemphigoid for several years now. However, comparative studies assessing the link between DPP‐IV inhibitor exposure and bullous pemphigoid have not yet been performed. Objectives: To detect, from the French Pharmacovigilance Database (FPVD), a signal of risk of bullous pemphigoid during DPP‐IV inhibitor exposure by comparative study. Methods: All spontaneous reports of DPP‐IV inhibitor‐related bullous pemphigoid recorded in the FPVD between April 2008 and August 2014 were described. We conducted disproportionality analyses (case–noncase method) to assess the link between DPP‐IV inhibitors and bullous pemphigoid, calculating reporting odds ratios (RORs). We also compared DPP‐IV inhibitor‐induced bullous pemphigoid reports rated per million defined daily doses dispensed during the study period. Results: Among 217 331 spontaneous adverse drug reaction reports registered in the FPVD, 1297 involved DPP‐IV inhibitors. Among these observations, 42 were bullous pemphigoid (vildagliptin, n = 31; sitagliptin, n = 10; saxagliptin, n = 1). The ROR for pooled DPP‐IV inhibitors was 67·5 [95% confidence interval (CI) 47·1–96·9]. Disproportionality was also observed for each DPP‐IV inhibitor: vildagliptin (ROR 225·3, 95% CI 148·9–340·9), sitagliptin (ROR 17·0, 95% CI 8·9–32·5) and saxagliptin (ROR 16·5, 95% CI 2·3–119·1). Analyses adjusted on dispensing data led to similar results. Conclusions: These data confirm a strong signal for an increased risk of bullous pemphigoid during DPP‐IV inhibitor exposure. This adverse drug reaction is observed for each DPP‐IV inhibitor, suggesting a class effect. The signal was higher with vildagliptin than with the other DPP‐IV inhibitors. Abstract : What's already known about this topic? Implication of dipeptidyl peptidase (DPP)‐IV inhibitors in bullous pemphigoid occurrence has been suggested in several case reports. What does this study add? There is a significant signal for an increased risk of bullous pemphigoid during DPP‐IV inhibitor exposure. This signal is outlined for each DPP‐IV inhibitor, suggesting a class effect. The signal of risk of bullous pemphigoid is higher with vildagliptin than with other DPP‐IV inhibitors.